Similar efficacy of thalidomide- and bortezomib-based regimens for first relapse of multiple myeloma - Krejci, Marta; Gregora, Evzen; Straub, Jan; Minarik, Jiri; Scudla, Vlastimil; Adam, Zdenek; Krivanova, Andrea; Pour, Ludek; Zahradova, Lenka; Buchler, Tomas; Mayer, Jiri; Hajek, Roman (Annals of hematology, 2011)
Many regimens containing novel drugs have been developed for multiple myeloma (MM). It is not yet clear whether some of the novel agents are better than others. In a retrospective study, we have analyzed the outcomes of patients with first relapse of MM treated with thalidomide-based (T) regimens (n=105) or bortezomib-based (B) regimens (n=106). Both T and B groups were comparable regarding basic clinical parameters and first-line therapies. Combination of thalidomide with an alkylating drug (A) and dexamethasone (D) was used in 91 cases, T with D in five cases, and T alone in nine cases. A combination of bortezomib with A and D was used in 58 patients, B with D or A in 40 patients, and B alone in eight patients. In the T group, ORR was 51%, median TTP from the start of treatment for relapse of 13.1 months, and median OS of 30.4 months. In the B group, ORR was 50% with median TTP of 16.7 months and median OS of 37.2 months. No significant differences in ORR (p=0.774), TTP (p=0.207), or OS (p=0.889) were observed between the two groups. In conclusion, T- and B-based regimens appear to be equally effective in the treatment of first MM relapse.
Keywords: Thalidomide; recidiva; dexamethason; inhibitory angiogeneze; Pyrazines; Humans; lidé středního věku; Multiple Myeloma; Female; Aged; dospělí; protokoly protinádorové kombinované chemoterapie; Antineoplastic Agents; výsledek terapie; senioři; lidé; bortezomib; mnohočetný myelom; Adult; kyseliny boronové; ženské pohlaví; Male; Middle Aged; Retrospective Studies; Bortezomib; Dexamethasone; Treatment Outcome; Angiogenesis Inhibitors; Antineoplastic Combined Chemotherapy Protocols; pyraziny; Aged, 80 and over; protinádorové látky; Recurrence; senioři nad 80 let; retrospektivní studie; Boronic Acids; míra přežití; mužské pohlaví; thalidomid; Survival Rate